Radical Democracy and the Internet
X, 251 p.
Keywords: In this systematic and mutual interrogation of radical democratic theory and Internet practice, contributors examine a range of democratic theories in relation to online communication and explore how such communication may advance democracy beyond what is conceptualized and practised within present liberal-capitalist political contexts.